The economics of paper consumption in offices - Shah, Iqtidar Ali; Amjed, Sohail; Alkathiri, Nasser Alhamar (Journal of Business Economics and Management, 2019)
This paper explores the factors potentially responsible for the overconsumption of office paper and estimates the adverse environmental and economic impact of overconsumption. Data were collected from the employees of selected higher educational institutions in Oman. Technical factors, workplace environment, printing preferences and lack of awareness were found the main cause of overconsumption. Environmental and economic impact of the paper was estimated from the actual amount of paper consumed using standard formulas from literature. The institutions have used 5,200 reams (13 tons) of 80gm A4 size paper in one year. The economic cost of the paper was 7,800 OMR (20,280 US$). The environmental impact estimated are: cutting of 312 trees, 73,970 Ibs of CO2 gas emission, 144,742 KWh of energy consumption, solid waste produced 29,614 lbs and 247975 gallons of water were wasted. Changing printing preferences, a significant amount of economic and environmental resources to the tune of 44.8% can be saved.